The Roots of Stereotype Threat: When Automatic Associations Disrupt Girls' Math Performance. Issue 1 (28th May 2013) - Galdi, Silvia; Cadinu, Mara; Tomasetto, Carlo
<x xml:space="preserve">Abstract</x> Although stereotype awareness is a prerequisite for stereotype threat effects (Steele & Aronson, 1995), research showed girls' deficit under stereotype threat before the emergence of math–gender stereotype awareness, and in the absence of stereotype endorsement. In a study including 240 six‐year‐old children, this paradox was addressed by testing whether automatic associations trigger stereotype threat in young girls. Whereas no indicators were found that children endorsed the math–gender stereotype, girls, but not boys, showed automatic associations consistent with the stereotype. Moreover, results showed that girls' automatic associations varied as a function of a manipulation regarding the stereotype content. Importantly, girls' math performance decreased in a stereotype‐consistent, relative to a stereotype‐inconsistent, condition and automatic associations mediated the relation between stereotype threat and performance.